ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LABA PADA PT.ASURANSI JIWA BERSAMA (AJB) BUMIPUTERA 1912 KPI SYARIAH PONTIANAK PERIODE 2013-2016 - B1031141004, Indah Purnama Sari (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The purpose of this research is to analysis the influence of the amount of income, amount of investment income, amount of cost, debt to equity ratio for the profit of PT. Asuransi Jiwa Bersama (AJB) Bumiputera 1912 KPI Syariah Pontianak periods 2013-2016. This research is quantitative research that use time series data from 2013-2016. Sample used in this research is financial statements of PT. Asuransi Jiwa Bersama (AJB) Bumiputera 1912 KPI Syariah Pontianak periods 2013-2016. Method used in this research is multiple linear regression method. The conclusions of this research are (1) the amount of income take the positive and significant effect on earnings state that income received by insurance give the positive influence on the company’s earnings. The received income give the direct influence on company’s earnings. (2) the amount of investment income take the positive and significant effect on earnings. State that investment is the one of the valuable asset owned by the company. The higher funds invested will give the positive signal for the growth company in the future. (3) the amount of the cost take the negative and significant effect on earnings. State that the cost should spended by the insurance company, give the negative effect on company’s earnings, the cost will make the earnings received by the company be reduced. (4) debt to equity ratio has no the significant effect on earnings. State that debt to equity ratio has no direct effect on insurance company’s earnings because in fulfilling the obligation, company use the funds derived from own capital and loans from bank and also the another financial institutions.Keywords:the amount of income, the amount of investment income, the amount of cost, debt to equity ratio.